Preventive effect of Oenothera rosea on N-methyl-N-nitrosourea- (NMU) induced gastric cancer in rats - Almora Pinedo, Yuan (2017)
Background: Currently, gastric cancer (GC) is considered a public health problem worldwide. Using medicinal plants for the prevention of chronic diseases such as cancer constitutes new alternatives in traditional medicine. Oenothera rosea (OR) could be an option, but it needs to be evaluated. Aim: The main objective of this study was to evaluate the protective effect of OR extract on N-methyl-N-nitrosourea (NMU)-induced GC in rats. Methods: In total, 80 male Holtzman rats were randomized into five groups. Group A received the saline solution (5mL/kg), group B received NMU 500 μg/kg (cancer inductor) by oral administration for 16 weeks, and groups C, D, and E were treated with OR extract (100, 200, and 300 mg/kg, respectively) and NMU in order to evaluate the preventive effect on cancer induced by NMU for 16 weeks. Blood and histological samples of stomachs were collected to determine histopathological, biochemical, and hematological parameters between different experimental groups. Results: Groups C, D, and E presented less histopathological changes such as anaplastic and hyperplastic cells, compared with group B. Hematological and biochemical parameters were recorded, and superoxide dismutase, malondialdehyde, and nitric oxide levels were statistically less than those of NMU group (P<0.05, P<0.01, and P<0.01). Conclusion: Considering the histopathological signs and the antioxidant activity in vivo as well as hematological and biochemical parameters of ethanolic extract of OR, we concluded that its administration in rats has a protective effect on GC, which is induced experimentally. This species could be studied in clinical trials for patients with GC in the future.